Technological human capital, firm innovativeness, and entrepreneurial success: the moderating role of seeking and receiving external funding. (2017) - Li, Huajing; Tang, Jintong
The majority of research on human capital has focused on the role of general human capital in organisational performance. Our study examines technological human capital, a form of specific human capital, and proposes that it is particularly important for entrepreneurial success in emerging economies such as China. We propose a multi-level and multi-stage theoretical model in which entrepreneurs' technological human capital positively impacts firm innovativeness and entrepreneurial success. Further, entrepreneurs' ability to seek and receive external funding positively moderates the effect of technological human capital on firm innovativeness and the influence of firm innovativeness on entrepreneurial success.